Iron Deficiency in Young Children and Methods of its Correction - I. N. Zakharova; A. N. Goryainova; E. B. Machneva; E. Yu. Dmitrieva; M. V. Mozzhukhina (Вопросы современной педиатрии, 2013)
Iron deficiency still presents an urgent problem in pediatrics. The paper presents both foreign and domestic data on prevalence of iron deficiency anemia and latent iron deficiency and methods of laboratory diagnostics of these states. Authors also discuss clinical presentations, long-term effects and modern approaches to treatment of iron deficiency states in children.